2008
DOI: 10.1063/1.3002299
|View full text |Cite
|
Sign up to set email alerts
|

Realization of defect-free epitaxial core-shell GaAs/AlGaAs nanowire heterostructures

Abstract: We report the controlled growth of vertically aligned GaAs/AlGaAs core-shell nanowires. By optimizing the shell deposition temperature and catalyst density we maintain high temperature stability and achieve defect-free epitaxial AlGaAs shell deposition with high aluminum incorporation. Energy dispersive x-ray analysis determines the shell composition to be Al0.9Ga0.1As and measures the uniformity of the shell thickness. Lattice-resolved high-angle annular dark-field scanning transmission electron microscopy im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 21 publications
1
67
0
Order By: Relevance
“…Previous studies have shown that the GaAs/AlGaAs core-shell NWs grow predominantly as cubic zinc-blende (ZB) single crystals, mainly along the <111> direction, perpendicular to the substrate surface [13,14]. Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the GaAs/AlGaAs core-shell NWs grow predominantly as cubic zinc-blende (ZB) single crystals, mainly along the <111> direction, perpendicular to the substrate surface [13,14]. Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Critical steps have been taken in these directions in the last years. Long single-crystal defect-free cores [6,7], selective radial doping [8], and lateral overgrowth with high-quality interfaces [9] have been successfully realized. Most importantly, complex radial modulation doped heterostructures are now being engineered in coremultishell NWs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…4 Refinements in the epitaxial growth of these nanowires are therefore essential in order for their optoelectronic and crystallographic standards to approach those of bulk material. 2,6,7 Such efforts are complicated by the fact that electrical measurements conducted on nanowires to determine charge-carrier mobility are often obscured by properties of the electrical contacts. Most contactless spectroscopic probes of nanowires to date have relied upon low-temperature photoluminescence measurements to characterize optoelectronic quality by measuring excitonic dynamics and radiative quantum efficiency.…”
mentioning
confidence: 99%